COMPARISON OF CARDIAC TROPONIN-I LEVELS IN POSTOPERATIVE PERIOD OF ON PUMP VERSUS OFF PUMP CORONARY ARTERY BYPASS SURGERY - Ullah, Kifayat; Waseem, Muhammad; Janjua, Asif Mahmood; Khadim, Shakila; Amin, Mashood Shahid; Ashfaq, Muhammad; Mustafa, Anum (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare cardiac troponin-I levels in post-operative period of on-pump (ONCAB) versus off-pump coronary artery bypass surgery.Study Design: Prospective Observational Study.Place and Duration of Study: Armed Forces Institute of Cardiology, from Jan 2019 to Dec 2019.Methodology: This prospective observational study was done at Armed Forces Institute of Cardiology from 1st January 2019 to 31st December 2019. Eighty six (43 in each on-pump and off-pump) patients admitted for elective coronary artery bypass grafting, aged 30-80 years were included in the study. Baseline data and cardiac troponin-I levels preoperatively as well as at 6, 12, 18 and 24 hours after the surgery in both groups were recorded and analyzed.Results: Out of 100 patients, mean age of the patients was 57.59 ± 10.24 years and 85% were males. All the base line characteristics, comorbid conditions and intra-operative findings were identical in both groups. There was marked rise in CK-MB levels postoperatively in overall participants. There was significant rise in Troponin I levels postoperatively in overall participants. Compared to OPCAB, postoperative Troponin I at 6hours and 12-hours was significantly higher in ONCAB.Conclusion: Compared to OPCAB, postoperative Troponin I at 6 hours and 12-hours was significantly high in ONCAB. However, there was no gross discrepancy in postoperative Troponin I levels between OPCAB and ONCAB at 18- & 24-hours after surgery.